2009
DOI: 10.1016/j.solener.2008.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a building integrated photovoltaic/thermal (BIPVT) solar collector

Abstract: The idea of combining photovoltaic and solar thermal collectors (PVT collectors) to provide electrical and heat energy is an area that has, until recently, received only limited attention. Although PVTs are not as prevalent as solar thermal systems, the integration of photovoltaic and solar thermal collectors into the walls or roofing structure of a building could provide greater opportunity for the use of renewable solar energy technologies. In this study, the design of a novel building integrated photovoltai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(90 citation statements)
references
References 14 publications
0
85
0
1
Order By: Relevance
“…There has also been efforts to create components for building integration. Anderson et al [127] developed a BIPV/T system for integration into roofs. The system was tested in an outdoor steady state test in New Zealand.…”
Section: Figure 19 Parabolic Trough Pv/t Collector Photo Courtesy Omentioning
confidence: 99%
“…There has also been efforts to create components for building integration. Anderson et al [127] developed a BIPV/T system for integration into roofs. The system was tested in an outdoor steady state test in New Zealand.…”
Section: Figure 19 Parabolic Trough Pv/t Collector Photo Courtesy Omentioning
confidence: 99%
“…It consists of flat-plate solar collectors, an external heat exchanger, a storage tank, and auxiliary heaters. In addition, this general configuration is also being employed and improved upon in other applications of solar energy systems, such as photovoltaic/thermal systems [17][18][19] and solar-driven heat and power systems [20]. The primary fluid, i.e., antifreeze fluid, circulates between the collectors and the hot side of an external heat exchanger.…”
Section: Mathematical Models Of Swh Systemmentioning
confidence: 99%
“…As such, it could be argued that the concentrator performs poorly when compared to purpose designed solar collectors with peak efficiencies in excess of 70%. However, this lower efficiency is due to the increased heat losses by radiation and convection in the absence of a glazing layer (Anderson et al, 2009) that reduce the thermal efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Previously Anderson et al (2009) had demonstrated the use of PVT collectors based on trapezoidal profiled long run metal roofs where passageways were formed in the trough of the roof profile for the thermal cooling medium to travel through. Subsequently, a cover having polycrystalline PV cells laminated to its surface was bonded into the trough, thus forming a tube to which heat could be transferred.…”
Section: Theoretical Assessment Of a V-trough Concentratormentioning
confidence: 99%